The Witcher or The Quack: what does twisting titles say about cognition and semantics? - Chudzik, Anna (Papers in Linguistics, 2025)
The article concerns the phenomenon of mistaken reconstruction from memory of linguistic information, such as the titles of films, TV series, novels, and plays. As specific proper names, these titles may be remembered either independently or within the broader context of knowledge about the work and the experience of its reception. In both cases, insufficient attention or elaboration during the process of encoding the title can lead to errors when recalling it. The aim of the study is to explore the cognitive-semantic nature of this phenomenon and to analyze its characteristic semantic constructions using tools from cognitive linguistics, including the concept of meaning as conceptualization, the notion of cognitive domains, and the model of meaning as scene construal. The material under scrutiny consists of examples of humorous memory errors – incorrectly recalled titles – that have been shared on social media. The analysis makes it possible to identify five recurring types of errors in title reconstruction, offering insight into the semantic cognitive mechanisms involved. These errors reflect universal cognitive-semantic and linguistic processes. Conclusions of the study indicate that the errors align with the claims of cognitive linguistics regarding cognition and semantics.